Analisis Situation Awareness pada Pilot Paramotor di Komunitas Paramotor Yogyakarta - Walid Jumlad; Aurelya Fauziyah Putri Efendi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the application of situation awareness among paramotor pilots in the Paramotor Community of Yogyakarta. Situation awareness refers to an individual’s awareness of environmental conditions that affect decision-making, especially in high-risk activities such as paramotor air sports. The research employs a qualitative case study approach. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that pilots in the community have optimally implemented the three levels of situation awareness: perception, comprehension, and projection. Pilots are able to identify critical elements in the flight environment, understand their impact on safety, and project potential scenarios to make accurate decisions. Experience, training, and systematic procedures are the key supporting factors in enhancing pilot situational awareness. These findings are expected to serve as a reference for evaluation and safety improvement in paramotor activities.